ANALYSIS ON FACTORS AFFECTING SOCIETY'S RESPONSE TO REALITY SHOW "MIKROFON PELUNAS HUTANG" AIRED BY INDOSIAR - Muhammad Hafizh Radritiawan (Metakom, 2018)
This research aims to determine the response of society to the tprogram of Microphone the Debt Repayment channel and to describe factors causing the response of society. The methods were conducted through observation, interview, and documentation. The sample was taken from society who lived on Purnawirawan Street I Gunung Terang Bandar Lampung. The result of this research was the external factor which influence the most was the frequency of people watching the program; while the internal factor consisted of the characteristics and the background of the society that eventually caused differences in the level of individual response. Overall, the response of society of this program was either positive: the society admitted that the show can trigger their empathy to help others in need, the program can make them to be more grateful, as a form of social entertainment, especially because it can entertain the audiences when the participants used the microphone to sing and responded negatively, tried to exploit the poor to make profit, while it lets the participants to complain easily and to give up to pay their debts. Keywords: Society's Response, Reality show, Factor Analysis